KOMUNIKASI KELUARGA DALAM PELESTARIAN BUDAYA SUKU KAILI DI KABUPATEN DONGGALA - Edwan; Donal Adrian (Kinesik, 2022)
Kaili culture is the creation of the Kaili tribal community which must be preserved from generation to generation by requiring the role of parents in teaching it. The local culture cannot be lost and must be maintained as a national characteristic. The purpose of the study was to determine family communication in the preservation of Kaili culture in Donggala Regency. The research method uses a qualitative type with a case study approach. Informant research subjects were selected purposively with data collection through in-depth interviews and direct observation. The analysis technique uses data reduction, data presentation, and conclusion drawing/verification. The results showed that family communication carried out by parents in preserving Kaili culture in children, namely (a) communicating using the Kaili language, (b) bringing children to weddings which were full of Kaili cultural displays, (c) teaching children about tabe, nosimpotove and nakapali, (d) providing an understanding of children related to percussion matters.